A peroxidase coordinating to Zn (II) preventing heme bleaching and resistant to the interference of H2O2. (24th September 2020) - Fu, Yaqi; Jiang, Zhengfeng; Feng, Wei
Abstract: Dehaloperoxidase (DHP) catalyzes detoxifying halophenols. It is a heme‐containing enzyme using H2 O2 as the oxidant. Heme bleaching from the active site is of great concern. In addition, the interference of DHP by H2 O2 leads to the inactivation of the enzyme. To solve these two problems, DHP is coordinated to Zn (II) in PBS buffer to form a biomineralized composite (DHP&Zn‐CP). DHP&Zn‐CP was characterized by measuring SEM and confocal images, as well as energy dispersive X‐ray spectrometry mapping. Fluorescence spectra demonstrated that DHP&Zn‐CP can prevent heme bleaching. Two‐dimensional FTIR spectra were measured, dynamically providing insight into the structural change of DHP along the coordination process. Raman spectra were performed to analyze the structural change. The optical spectra confirmed that the forming of DHP&Zn‐CP had a little effect on the structures of DHP. For the dehalogenation of 2, 4, 6‐trichlorophenol, DHP&Zn‐CP can tolerate the presence of H2 O2 and is resistant to the interference by H2 O2 . The catalytic efficiency of DHP&Zn‐CP is much higher than that of free DHP.